A Ce(OTf)3/PyBox catalyzed enantioselective Hosomi–Sakurai reaction of aldehydes with allyltrimethylsilane. (7th August 2015) - Zhao, Song; Zhang, Xulong; Zhang, Yuwei; Yang, Huanhuan; Huang, Yan; Zhang, Kui; Du, Ting
Abstract : An approach to the efficient synthesis of enantioselective homoallylic alcohols has been developed by the use of a catalytic amount of a cerium/PyBox complex. Abstract : An efficient enantioselective Hosomi–Sakurai reaction catalyzed by a chiral Ce(OTf)3 /PyBox complex has been explored. In the presence of 20 mol% of a chiral catalytic complex prepared in situ from Ce(OTf)3 and 2, 6-bis[( S )-4-isopropyloxazolin-2-yl]pyridine {( S )-i-Pr-PyBox} or tetraphenyl substituted ( S )-i-PrPyBox, the enantioselective allylation of aldehydes with allyltrimethylsilane proceeded smoothly at room temperature and provided the homoallylic alcohols in good yield (up to 95%) and excellent enantioselectivities (up to 99%).